2020
DOI: 10.1016/j.omtm.2020.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Cell Therapy by Ectopic Hepatocyte Transplantation Treats the Porcine Tyrosinemia Model of Acute Liver Failure

Abstract: The effectiveness of cell-based therapies to treat liver failure is often limited by the diseased liver environment. Here, we provide preclinical proof of concept for hepatocyte transplantation into lymph nodes as a cure for liver failure in a large-animal model with hereditary tyrosinemia type 1 (HT1), a metabolic liver disease caused by deficiency of fumarylacetoacetate hydrolase (FAH) enzyme. Autologous porcine hepatocytes were transduced ex vivo with a lentiviral vector carrying the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…The native tyrosinemic liver was still highly involved in bilirubin and bile acid metabolism and transport. Given that the ectopic livers did not have a biliary system connected to the intestine [5,6] and no accumulation of bile, [7,8] the evidence suggested that hepatocytes in the ectopic livers were actively transporting bile to the intestine, possibly through the bloodstream using the remnant native tyrosinemic liver. Our previous work in the mouse [5,6] and our two recent reports in the pig on the ectopic liver [7,8] concurred with the notion that bile acids and bilirubin are transported outside of the ectopic livers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The native tyrosinemic liver was still highly involved in bilirubin and bile acid metabolism and transport. Given that the ectopic livers did not have a biliary system connected to the intestine [5,6] and no accumulation of bile, [7,8] the evidence suggested that hepatocytes in the ectopic livers were actively transporting bile to the intestine, possibly through the bloodstream using the remnant native tyrosinemic liver. Our previous work in the mouse [5,6] and our two recent reports in the pig on the ectopic liver [7,8] concurred with the notion that bile acids and bilirubin are transported outside of the ectopic livers.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] However, most patients with severe liver disease have fibrotic and cirrhotic liver obstructing blood flow, which constitutes an adverse environment for liver regeneration. Our group has previously demonstrated that lymph nodes (LNs) are excellent extrahepatic sites for ectopic liver development [5][6][7][8] as well as for other tissues, [9][10][11][12] and direct injection of hepatocytes into LNs resulted in the formation of a functional ectopic liver. [6] When transplanted into the peritoneal cavity, hepatocytes migrated to the abdominal LNs to generate ectopic livers.…”
Section: Introductionmentioning
confidence: 99%
“…Tbx3 , OC1/2 , Mab21l2 , and UbC have never been tested as targets for blastocyst complementation. Fah is an appealing target for blastocyst complementation for several reasons, including the well-described ability of Fah −/− livers to host the development of WT hepatocytes, whether the WT cells are introduced through genetic reversion or via deliberate transplantation ( Nicolas et al., 2020 ; Overturf et al., 1996 ; Zhang et al., 2016 ).…”
Section: Fah −/− Animals As Recipients For Blastocyst Complementationmentioning
confidence: 99%
“…In the 1990s, it was observed that children with HT1 commonly had spontaneous reversion of the FAH mutation in hepatocytes, causing overgrown nodules of normal tissue in their livers as the reverted hepatocytes out-competed those damaged by FAA accumulation ( Kvittingen et al., 1994 ). Subsequent experiments demonstrated that exogenously introduced WT hepatocytes can repopulate Fah −/− livers in mice, rats, and pigs ( Hickey et al., 2016 ; Nicolas et al., 2020 ; Overturf et al., 1996 ; Zhang et al., 2016 ). Human hepatocytes and hepatocyte-like cells can be infused into immunodeficient Fah −/− mice, repopulating the liver with human hepatocytes ( Azuma et al., 2007 ; Bissig et al., 2010 ; Bissig-Choisat et al., 2016 ; Yuan et al., 2018 ).…”
Section: Fah −/− Animals As Recipients For Blastocyst Complementationmentioning
confidence: 99%
“…To date, experimental approaches to treat tyrosinemia type 1 involve adenovirus- and AAV-mediated gene transfer, 13 , 14 gene delivery of naked DNA constructs, 15 , 16 genome editing, 17 , 18 , 19 and ex vivo therapy. 20 , 21 , 22 The approach presented herein focuses on mRNA-based therapy, a powerful tool with tremendous potential to treat a variety of indications; e.g., infectious diseases, personalized cancer therapy, protein replacement therapy, and gene editing. 23 , 24 , 25 …”
Section: Introductionmentioning
confidence: 99%